Spectrum of Haematological malignancies managed at tertiary centre: A one-year retrospective review (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Hematological malignancies are not uncommon and all ages and genders are affected. Hematological malignancies are a group of cancers that arise from a malignant transformation of cells of the bone marrow or lymphatic system. There are several classification systems for Hematological Malignancies. The WHO classification was the first worldwide consensus classification on hematological tumors.Methods: We retrospectively collected data from the Department of Pathology and Hematology Unit of Internal medicine from 2015 to 2016. Hematological malignancies were analyzed clinically and with laboratory parameters. They were initially analyzed with complete blood counts and peripheral smear and diagnosed on the basis of Bone marrow morphological assessment, Immunophenotyping and cytogenetic and molecular markers and histopathology and Immunohistochemistry of Excised lymph node when applicable. Plasma cell dyscrasias were assessed clinically for features of CRAB (hypercalcemia, renal impairment, anemia and lytic lesion) and evaluation was done by hemogram, biochemical parameters and skeletal survey. Later plasma cell dyscrasias was diagnosed on the basis of bone marrow study, Immunofixation electrophoresis, serum free light chain assay, serum protein electrophoresis and myeloma defining events.Results: There were 110 cases of hematological neoplasm from Feb 2015 till Jan 2016. Lymphoid neoplasm was the commonest hematological malignancies with 60.9% followed by myeloid neoplasm of 37.3% then histiocytic neoplasm of 1.5%. Median age at diagnosis for all Hematological malignancies was 55 years of age. In patients under 20 years of age, T ALL and LCH accounted each with o.9%. In young adult Patient, NHL was the most common HM whereas; MPN was the most common HM in adults. In older patients, PCN was the most common HM. Male were more prevalent than female in Hematological malignancies. Male accounted for 73.6% and female were 26.4% with male female ratio 2.7:1. In both male and female, Lymphoid Neoplasm was most frequent HM. In male PCN was the most frequent HM. In female, NHL, PCN and MPN was the most frequent HM. Lymphoid neoplasm included Mature B cell Neoplasm (MBCN) 43.6%, Acute Lymphoblastic Leukemia (ALL) 7.3%, Hodgkins Lymphoma (HL) 5.5% and Mature T cell Neoplasm (MTCN) 3.6%. Plasma cell Neoplasm (PCN) (29%) was the commonest lymphoid neoplasm. Among the myeloid neoplasm (MN), Myeloproliferative neoplasm (MPN) accounted 19.1% followed by acute myeloid leukemia (AML) with 14.5% then Myelodysplastic syndrome (MDS) 4.5%. Chronic Myeloid Leukemia (CML) is the commonest HM among different subtypes of MPN.Conclusion: HM can occur at any age group with median age at diagnosis of 55 years. Overall men are more affected with HM than women. In both male and female Lymphoid malignancies are frequent HM. There is difference in distribution pattern and subtypes of Hematological malignancies at different age group.